PENGARUH FAKTOR PRIBADI DAN FAKTOR SOSIAL TERHADAP PROSES KEPUTUSAN PEMBELIAN PRODUK FASHION DAN BEAUTY PENGGUNA PERSONAL SHOPPER (Study pada Jasa Titip @titipall) - Dynda Nazwa Prameizuari; Kristina Sisilia; Hidayat, Agus Maolana (ITB AAS Indonesia Surakarta, 2024)
The popularity of social media platforms is one of the attractions for its users. This phenomenon is proof that the existence of social media platforms can be a one-step journey solution for the majority of users to meet their needs. The presence of @titipall jastip can answer this problem, because all needs can be met by only paying jastip fees and shipping costs. This study aims to determine the partial and simultaneous influence of personal factors and social factors on the purchasing decision process of jastip @titipall personal shopper users. This research method uses quantitative methods with descriptive analysis types, data analysis techniques using multiple linear regression analysis. The population used is followers of @titipall's tipping service, which amounts to 4,520. The sampling technique is non-probability sampling and the sampling technique uses purposive sampling method with a sample of 104 respondents, namely consumers who have purchased an item using jastip @titipall. The results of this study indicate that personal factors have a percentage of 84.2%, social factors have a percentage of 84.2%, the purchasing decision process has a percentage of 84.1%, so that all of them are in the very good category. Based on the research results partially and simultaneously, it shows that personal factors, social factors, and the purchasing decision process have a positive and significant effect.